Thirty Years Later: What Has Craniofacial Distraction Osteogenesis Surgery Replaced?. Issue 6 (June 2020) - Hopper, Richard A.; Ettinger, Russell E.; Purnell, Chad A.; Dover, M. Stephen; Pereira, Alberto Rocha; Tunçbilek, Gökhan
Abstract : Learning Objectives: After studying this article and viewing the video, the participant should be able to: 1. Compare the relative stability and neurosensory changes following mandible distraction osteogenesis with those after traditional advancement and fixation. 2. Describe the condylar changes that can occur after mandible distraction osteogenesis and list three ways to mitigate these changes. 3. Propose clinical situations where segmental or rotational movements of the midface may allow improved outcomes compared to en bloc linear distraction advancement. 4. Summarize the advantages and risks associated with anterior and posterior cranial distraction osteogenesis compared to traditional one-stage expansion. Summary: Over the past 30 years, distraction forces have been applied to the spectrum of craniofacial osteotomies. It is now time to assess critically the current understanding of distraction in craniofacial surgery, identifying both traditional procedures it has replaced and those it has not. This article provides a review of comparative studies and expert opinion on the current state of craniofacial distraction compared with traditional operations. Through this critical evaluation, the reader will be able to identify when distraction techniques are appropriate, when traditional techniques are more favorable, and what the future of distraction osteogenesis is.